Efeito da aeração e do tempo de ciclo na remoção biológica de nitrogênio de efluente da indústria avícola - Lopes, Carla Limberger (2011)
This study aimed to evaluate the influence of air flow (0.25, 0.50 and 0.75 L.min-1.Lreator-1) and cycle time (11.35 h, 15.15 h and 18.25 h) in the performance of a sequencing batch reactor (SBR) to promote nitrification and denitrification of wastewater from slaughterhouse's poultry and refrigerator. The operation included the steps of feeding, aerobic and anoxic reaction, sedimentation, discharge and rest. SBR was operated on a laboratory scale with a working volume of 4 L, keeping 25% of biomass retained in the reactor as an inoculum for the next batch. The "manipueira" was added as a carbon source at the beginning of anoxic phase in order to keep the C: N ratio between 5 and 6. During this process, parameters monitored included: pH, alkalinity, dissolved oxygen and temperature. It was developed a factorial design (22) with five repetitions at the central point to check the influence of the response variable removal of total inorganic nitrogen (NH4+-N + NO2--N + NO3--N) in the whole process (%). Data were analyzed with 95% confidence, and experimentally, a higher removal of total inorganic nitrogen (85.75%) on average was observed when using air flow of 0.50 L.min-1.Lreator-1 in time cycle of 15.15 h. However, there was no statistically significant factor for the air flow, and during the progress of study, this variable was kept stable at 0.25 L.min-1.Lreator-1 while the cycle time was gradually increased until efficiency in the removal of constant nitrogen could be observed, which occurred at time 15.1 h with 92.78% in removal efficiency of total inorganic nitrogen.